Artificial Intelligence: Illuminating the Future of Periodontology (Update Dental College Journal, 2024)
AIMS & OBJECTIVES : The application of computer systems to simulate human behavior is known as artificial intelligence (AI). Periodontitis, a prevalent condition worldwide, leads to the deterioration and eventual loss of the tissues supporting teeth. Its diagnosis and treatment are increasingly being supported by AI as a valuable tool for medical practitioners. The objective of this study is to evaluate existing literature concerning the utilization of AI in both the diagnosis and epidemiological analysis of this disease.MATERIAL & METHOD: After a thorough search in April 2023, 50 papers were found that needed to have their abstracts screened after duplicates were removed. The publications that were chosen covered a broad spectrum of subjects, however the input data and photos were mostly focused on visual imaging.RESULT: Over the last ten years, the field has experienced substantial expansion, but the variety of statistical tests available for research has resulted in inconsistent reporting of results. It is essential to standardize reporting techniques and methodology to allow meaningful comparisons. By doing this, it will be possible to fully utilize AI's potential to enhance periodontics and implantology diagnosis and therapy.Update Dent. Coll. j: 2024; 14(1):31-35